Correlação entre os glicosaminoglicanos, proteoglicanos e colágenos e a gravidade da doença de Dupuytren - Lenzi, Luiz Guilherme De Saboya [UNIFESP] (2023)
Introduction: Dupuytren's disease (DD) is a typical fibroproliferative condition of the hand resulting from genetic, epigenetic, and environmental factors. Its origin is related to the synthesis of extracellular matrix (ECM), a complex network of different types of macromolecules. Changes in its content and arrangement impact normal physiological processes and pathological conditions. Objective: To correlate glycosaminoglycans, proteoglycans, and collagen in the ECM of patients with different clinical stages of DD. Methods: The study involved 14 patients categorized into four groups based on their stages: I, II, III, and IV. Molecules in palmar fascia biopsy and urine samples were analyzed using chromatographic methods, RNA analysis, protein detection in confocal microscopy, and Coherent antistokes Raman scattering (CARS) microscopy. Results: Significant changes in the content and arrangement of chondroitin sulfate, dermatan sulfate, and collagen were observed in the palmar fascia of patients compared to normal tissue, regardless of the degree of disease. For the first time in the literature, It was possible to significantly associate expression of versican, aggrecan, and decorin. In addition, the excretion of hyaluronic and sulfated glycosaminoglycans is significantly decreased in the urine of DD patients. Conclusion: The data indicate that proteoglycans and collagen arrangement are possible markers of the disease stage. Furthermore, the decreased urinary excretion of glycosaminoglycans suggests a systemic effect of the disease.